The Roots of Indonesia's Resilience Against Violent Extremism - Jamhari Jamhari; Testriono Testriono (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2021)
This article explores Indonesia’s institutional foundations to understand the country’s resilience against violent extremism. First, Pancasila has been the foundation of an inclusive state that can bind Indonesian diversity. Second, multiparty elections allow Islamist groups to participate in politics and express their aspirations constitutionally, thus moderating their violent strategies. Third, the support of the largest Islamic organizations, especially NU and Muhammadiyah, for counterterrorism and law enforcement against extremist orchestrated by the government. Both organizations exhibit a stronghold essential to countering the Salafi jihadist ideology. However, although infrequent and small in scale, the continued acts of violent extremism in Indonesia have shown that there is still room for the terrorist ideology to grow. Some Islamic educational institutions deliberately educate students to support Islamism, and some students are introduced to Salafi jihadist ideology. Such a development should serve as a warning for the government to pay more attention to the curriculum and teachers, especially in Islamic educational institutions.